The Prevalence of Multi-Type Infections Among Human Papillomavirus Types in Korean Women - Jang Mook Kim; Hee Seung Song; Jieun Hwang; Jae Kyung Kim (Pathogens)
The distribution of human papillomavirus (HPV) genotypes shows inconsistencies across countries, ethnicities, and socioeconomic levels. An in-depth identification of HPV infection rates and genotypes across regions, ethnicities, and age groups in large populations is crucial. We aimed to assess the prevalence of HPV infections among Korean women and investigate the prevalence of multi-type infections among HPV types. To identify HPV types, 16,669 specimens were subjected to DNA extraction and real-time polymerase chain reactions. The HPV infection rate was 36.7%, with single- and multi-type HPV infection rates of 21.4% and 15.3%, respectively. The prevalence of HPV infection was higher among women in their 20s and 60s. HPV types 16 and 18 were most commonly multi-type infected with HPV type 52. In conclusion, promoting HPV awareness and prevention strategies and incentivizing vaccination can boost vaccination rates among eligible individuals.